Cost-Effectiveness of the 13-Valent Pneumococcal Conjugate Vaccine in Children in Portugal - Gouveia, M (2019)
Pneumococcal infections are the leading cause of vaccine-preventable death in children. In June 2015, the 13-valent pneumococcal conjugate vaccine (PCV13) was introduced in the Portuguese Immunization Program. We evaluated the cost-effectiveness of children vaccinated with PCV13 versus no vaccination for preventing pneumococcal diseases.